PERBANDINGAN METODE PEMBEBANAN VAKUM DENGAN PRAPEMBEBANAN UNTUK MEMPERCEPAT PROSES KONSOLIDASI ( 17-23 ) - Metri Harissa; Mutiara FitriWahyu Ningrum; Sukarman Sukarman; Ika Sulianti (PILAR, 2018)
Palembang Toll Development Project - Simpang Indralaya is built on swamp land. The subgrade of this road is soft clay soil that has low bearing capacity of soil. Low bearing capacity of the soil will cause severe damage to the pavement on the soil heap. Therefore it is necessary to strengthen the base soil to be able to withstand and avoid sliding because it does not decrease.In this final project, there will be comparative analysis of 2 (two) alternatives to improve the embankment in reaching the same degree of consolidation. The first alternative is traditional preloading method and second alternative is vacuum preloading method.From the calculation results, obtained by using vacuum preloading method, the time required to achieve the same degree of consolidation can be shorter than the traditional preloading method.